The Effect of Diet on the Microbiome Composition and Incidence of NNK-Induced Lung Cancer. (29th May 2020) - Elisia, Ingrid; Hay, Mariah; Li, Michael; Cho, Brandon; Lam, Vivian; Mohn, William; Leung, Hilary; Krystal, Gerald
Abstract: Objectives: Since lowering carbohydrate (CHO) intake has been hypothesized to reduce cancer risk, we investigated whether low-CHO diets could prevent lung cancer in A/J mice, induced by the tobacco-specific carcinogen, 4-(N-methyl-N-nitrosamino)-1-(3- pyridyl)-1-butanone (NNK), and, if so if this corresponded to changes in gut microbiome composition. Methods: We compared the effect of different quantities and types of CHO (easily digestible vs resistant), protein (casein vs. soy) and fat (fish vs. coconut vs. a mixture of oils) in modulating lung nodule formation and gut microbiome composition in A/J mice. Mice were fed either the Western diet or the low CHO diets, composed of different types of CHO, protein and fat for two weeks before injections with NNK to initiate lung formation. After 20 weeks, their feces were collected for amplification and sequencing of the bacterial 16S RNA gene V4 regions and the lung nodules were counted. Results: Diets low in easily digestible starch, high in fish oil and soy protein were the most effective at preventing the formation of NNK-induced lung nodules. Changing protein, CHO and fat type in the diets all resulted in significant differences in the fecal microbiome composition of the NNK-injected mice. We also found a reduced abundance of the Streptococacceae and Clostridiaceae families in mice with low lung nodule numbers. Conclusions: We suggest that it is possible that the diets reduced lung nodule formation, at least in part, via alterations in the microbiomes of the mice. Funding Sources: Lotte & John Hecht Memorial Foundation.